2019
DOI: 10.1096/fj.201901606r
|View full text |Cite
|
Sign up to set email alerts
|

The classic metal‐sensing transcription factor MTF1 promotes myogenesis in response to copper

Abstract: Metal-regulatory transcription factor 1 (MTF1) is a conserved metal-binding transcription factor in eukaryotes that binds to conserved DNA sequence motifs, termed metal response elements. MTF1 responds to both metal excess and deprivation, protects cells from oxidative and hypoxic stresses, and is required for embryonic development in vertebrates. To examine the role for MTF1 in cell differentiation, we use multiple experimental strategies [including gene knockdown (KD) mediated by small hairpin RNA and cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 145 publications
6
88
0
Order By: Relevance
“…Interestingly, treatment with As 2 O 3 clearly increased MTF1 expression. In addition, apocynin, a NADPH oxidase inhibitor, eliminated this increase of MTF1 expression, consistent with the reports of Tavera-Montanez et al that MTF1 levels were increased following exposure to toxic heavy metals [ 44 ]. Furthermore, we found that MTF1 knockdown eliminated the As 2 O 3 -induced increase of lncRNA OTUD6B-AS1 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, treatment with As 2 O 3 clearly increased MTF1 expression. In addition, apocynin, a NADPH oxidase inhibitor, eliminated this increase of MTF1 expression, consistent with the reports of Tavera-Montanez et al that MTF1 levels were increased following exposure to toxic heavy metals [ 44 ]. Furthermore, we found that MTF1 knockdown eliminated the As 2 O 3 -induced increase of lncRNA OTUD6B-AS1 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Mouse embryos lacking MTF-1 show embryonic lethality probably due to the dysregulation of γ-glutamylcysteine synthetase ( γ-GCS ), an essential MTF-1 target gene in glutathione biosynthesis ( 27 ). A recent study demonstrated that MTF-1 regulates myoblast differentiation via direct interaction with the myogenic gene promoter ( 28 ). These studies suggest that MTF-1 is an important factor involved in the regulation of a diverse set of genes, thereby protecting cells from various stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we found that several TFs have known roles in the stage in which they are found significant, e.g., Nfe2fl2 in ESC and pre-IPSC module 6, which is known to play an important role in the embryonic stem cell state [17], and Mycn and Esrrb in the pre-IPSC module 6, which are both known to be important for early embryonic stages. We also found several muscle and mesodermal factors associated with MEF (Foxl1 [18], Mtf1 [19] in module 6), MEF48 (Osr1 [20], Left1 [21] in module 5), and both MEF and MEF48 (Sox5 [22] in module 5).…”
Section: Using Drmn To Gain Insight Into Regulatory Programs Of Cellular Reprogrammingmentioning
confidence: 81%